Enumeration 2024: What We Know and What We Wish We Knew About the Governmental Public Health Workforce in a COVID-19 Recovery Landscape - Leider, Jonathon P.; Balio, Casey P.; Hogg-Graham, Rachel; Weiss, Nicole M.; Vogel, Abby; Onal, Sezen O.; Zang, Xiao; Kett, Paula; Edmonds, Joyce; Karnik, Harshada; Dockery, Nathan; Joseph, Bibin; et al. (American journal of public health (1971), 2025)
Objectives. To expand on previous enumerations by assessing the size and composition of the governmental public health workforce in the wake of the COVID-19 pandemic, identifying workforce trends, occupational distributions, and potential gaps in staffing. Methods. From 2023 to 2024, using 2022 data in the United States, we conducted 3 distinct analyses: (1) estimating the total workforce size, (2) profiling occupation-specific distributions, and (3) evaluating the role and prevalence of public health nurses using novel data sources. For total counts, we used multiple imputation by chained equations to develop robust agency-level estimates and address missingness from multiple data sets. Results. State and local public health agencies grew to approximately 239 000 staff in 2022, up from an estimated 206 500 in 2019. The largest occupation groups included office and administrative support workers (37 576) and public health or community health nurses (29 387). We found that 73 478 (1.8%) of registered nurses nationwide served in governmental public health roles. Conclusions. The size of the workforce during the COVID-19 response has returned to 2008 levels although temporary staff largely constitute the increase. Public Health Implications. An undersized workforce leaves the United States vulnerable to future disasters and current challenges. ( Am J Public Health. 2025;115(5):707–715. https://doi.org/10.2105/AJPH.2024.307960 )